1985: Learning to Learn: language & study skills in context: Proceedings of the 6th Annual Australasian Study Skills Conference - Quintrell (Editor), Neil (Journal of Academic Language and Learning, 2026)
Formatting note: In the pdf, an article can be accessed directly by clicking on its title in the table of contents or via the Bookmarks pane. Introduction … iv Study Skills Development and Academic Chauvinism: Beasley, Vic … 1-16 A Distance Education Strategy for Assisting Learners Bridge the Gap to Tasmanian Higher Education: Cost Effective Study Skills Options to Overcome Institutional Presdigitation, Pious Principles or Procrastination: Brown-Parker, John and Judi … 17-34 The Use of Self-Help Resources in Developing Language Skills: Clayton, Jean … 35 English for Academic Purposes: Deravin, Garnet … 37-48 Towards Understanding the Library’s Part in Tertiary Study Skills: Duncan-Kemp, Dawn … 49-52 Helping Students Write: What Help Can Be Given and Who Can Give It? Hancock, Joelie … 53-60 Intonation and the Non-Native Speaker: Lasserre, Barbara … 61 The Instructional Design of ’Facets of Learning’, An Audio-Based Program to Teach Study Skills: Lewis, Justus H. … 63-69 Write It! Then Get It Right! Suggestions for Assessing, Programming and Teaching Assignment Writing Skills at Tertiary Level: McEvedy, M. Rosanna … 71-83 Things Invisible to See: Meyer, Rosalind S. … 85-96 What Do Academic Staff Mean When They Claim Students Can’t Write? Nightingale, Peggy … 97 The Problem of the Tertiary Dyslexic: Noble, Ann … 99-105 Do Study Skills Help Students to Learn More Effectively? Ramsden, Paul … 107 Study Skills Training Within a Counselling Service: Taylor, Diana … 109—113 Advanced Communication Skills and Report Writing Course: Todd, Shona … 115-132 Validation or Valediction: Analysis of an Effective Reading Course: Wilson, Rosemary J. … 133-135 The Use of the Repertory Grid Technique in a Study of Postgraduate Students’ and Supervisors’ Personal Constructs of Research: Zuber-Skerritt, Ortrun … 137-143 Consideration of the Use and Measurement of One Form of Tertiary Skills: Essay Assignment Skills: Elms, John … 145-152 Towards Tailoring Study Skills to Counter Tertiary Student Withdrawal or Failure: Olsen, Peter and Elms, John … 153-158 A Summary of the Provision of Learning and Language Skills Support in Australian Universities: 1985: Quintrell, Neil … 159